Increased sortilin and its independent effect on circulating proprotein convertase subtilisin/kexin type 9 (PCSK9) in statin-naive patients with coronary artery disease. (15th January 2017) - Hu, Die; Yang, Yang; Peng, Dao-quan
Abstract: Background: Proprotein convertase subtilisin/kexin type 9 (PCSK9) has been shown to play a crucial role in the metabolism of low density lipoprotein receptor (LDLR). Sortilin, encoded by the dyslipidemia-related gene SORT1, is also an important regulator of lipoprotein metabolism. Animal studies have shown the potential role of sortilin in regulating secretion of PCSK9. However, the data for the relationship between serum sortilin and circulating PCSK9 in CAD patients are scarce. Methods: Eighty subjects were classified into a CAD group (n = 43) and a non-CAD group (n = 37) according to their clinical conditions and the results of coronary angiography (CAG). Serum PCSK9 and sortilin levels were measured with enzyme-linked immunosorbent assays. Results: CAD patients had markedly greater PCSK9 concentrations than controls [247.0(218.6317.4) vs 226.6(181.6270.3) ng/ml, P = 0.007]. Moreover, serum PCSK9 levels were still higher in patients not receiving statin therapy, as compared with those in the control group [261.8(216.0, 315.8) vs 221.0(176.8260.7)ng/ml, P = 0.003]. Circulating sortilin tended to be higher in CAD patients than in non-CAD subjects, yet the difference is significant only between the statin-naive CAD patients and controls [4.96(4.38, 6.57) vs 4.28(2.96, 5.03) ng/ml, P = 0.032]. Serum PCSK9 concentrations were positively associated with sortilin levels(r = 0.37, P = 0.001, n = 80). Stratified analysis showed that there was stronger correlation between PCSK9 and sortilin in non-statin group (r = 0.41, P = 0.001, n = 60) as well as in the non-CAD group (r = 0.47, P = 0.004, n = 37), whereas the correlation between them was disappeared in statin group and CAD group. Using stepwise multiple regression analysis with adjustment for age, gender, LDL-cholesterol, smoking and CAD, we found that the correlation between serum sortilin and PCSK9 levels remained significant in all subjects (P = 0.01) as well as in statin-naive group (P = 0.03). Conclusion: Both circulating PCSK9 and sortilin levels are elevated in CAD patients. PCSK9 was independent related to sortilin, but their correlation was affected by the use of statin therapy.